The Effect of Work Life Balance and Work Attachment on Organizational Citizenship Behavior: The Mediation Role of Job Satisfaction - Prima Akbar Mashudi*; Rezi Erdiansyah (Universitas Syiah Kuala, 2023)
Good governance requires an improved bureaucracy that understands the various wishes of the community, especially related to public services, so that the Human Resources (HR) of government officials have an important role in achieving good governance. The emergence of disparities in behavior that prioritizes their own or group tasks, different acceptance if there are additional tasks outside their main duties, objections if required to work outside working hours shows that there are still problems related to organizational citizenship behavior. The purpose of this study was to determine the direct effect of work-life balance and work attachment on organizational citizenship behavior, as well as the indirect effect of work-life balance and work attachment on organizational citizenship behavior through job satisfaction of civil servants at the Directorate General of Intellectual Property. The research method used is quantitative research using survey techniques and questionnaires on civil servants at the Directorate General of Intellectual Property with a sample of 235 respondents. Data analysis using Structural Equation Modeling (SEM) with SmartPLS v.3.2.9 software. The results showed that work-life balance and work attachment have a positive and significant direct effect on organizational citizenship behavior and a positive and significant indirect effect through job satisfaction .